Repair method of micro-metal network structure based on electrochemical deposition
Through electrochemical deposition technology, the defect area of the micrometal network structure is repaired, and the problem of poor conductivity and light transmittance caused by surface defects and holes of the micrometal network structure is solved, and the effect of improving conductivity and light transmittance is achieved.
Patent Information
- Application Number
- CN202510152373.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-14
AI Technical Summary
The surface of the micrometal network structure prepared in the prior art is prone to defects and holes, resulting in poor conductivity and light transmission, and difficult to repair through the process, affecting the performance and reliability of the device.
Using the micrometal network structure repair method based on electrochemical deposition, the micrometal network structure is effectively repaired by configuring the electrolyte mixture liquid and repairing it in the electrochemical deposition equipment, and the difference in electric field distribution is used to carry out directional deposition in the defect area, so as to achieve effective repair of the micrometal network structure.
This method can accurately perform material deposition at defects in micrometal network structures, realize directional repair, improve conductivity and light transmittance, and enhance the overall performance and reliability of the device.
Smart Images

Figure CN119615314A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of transparent conductive material repair, and in particular to a repair method for a micro-metal network structure based on electrochemical deposition. Background Art
[0002] With the rapid development of electronic technology, micro-metal network structures have shown broad application prospects in the fields of flexible and stretchable electronic devices and microwave transparent electrostatic shielding. Micro-metal network is a nano- or micron-scale network structure composed of metal lines, which is usually used for conductive or optoelectronic functions in electronic devices. It achieves electrical conductivity, light transmittance and mechanical flexibility through a metal structure formed on the surface of a substrate or a film. The construction of micro-metal networks can adopt a variety of techniques, such as cracked film lithography, wet deposition, magnetron sputtering, etc. Through these methods, metal materials (such as copper, silver, aluminum, etc.) are deposited in predetermined areas to form an interwoven micro-wire network. The micro-metal network structure has conductivity and transparent plates, and is stretchable. It can replace traditional transparent thin film conductive electrodes and avoid the performance failure of traditional thin film transparent conductive electrodes (such as ITO and FTO, etc.) due to cracking during stretching and bending. At the same time, the micro-metal network also has excellent electromagnetic shielding performance. It transforms the traditional metal shielding structure into a transparent shielding structure by breaking the whole into parts, and shows broad application prospects in transparent microwave devices, confidential conference rooms, aviation vehicles, unmanned driving, electromagnetic shielding and anti-magnetic explosion design of drones.
[0003] At present, the preparation methods of micrometal network structures mainly include photolithography (semiconductor photolithography or electron beam lithography), PS ball template method, crack template method and solution self-assembled nanowire method. However, the main problems faced by the above methods are often that it is difficult to achieve large-area preparation, or the prepared micrometal network has poor conductivity and unstable performance. These problems are mainly because it is difficult to take into account the conductivity and transparency of the micrometal network in the preparation process when preparing the micrometal network structure. For example, when the prepared micrometal network is too thick, it cannot be photolithographically developed; when it is too thin, the conductivity is insufficient. Although increasing the line width of the metal wire during the preparation process can improve the conductivity of the prepared micrometal network, it will cause the transmittance to fail to meet the requirements. The metal nanowire structure represented by silver nanowires has advantages in preparation area and process economy, but the connection between the silver nanowires is unstable, the contact resistance is large, and it is easy to be oxidized, so that the prepared silver metal network structure cannot achieve high transparency, high conductivity and high stability at the same time.
[0004] Therefore, the micrometal network prepared by the existing preparation method will have defects and holes on its surface. These defects include fractures of the micrometal network, discontinuous areas, and local weakness of the metal layer. These defects are difficult to repair through the process, so they will significantly reduce the conductivity and light transmittance of the prepared micron metal, thereby affecting the overall performance and reliability of the device prepared by the micrometal network. In addition, due to the influence of Joule heat effect and tensile bending, the micrometal network with defects and holes on the surface is very easy to break during use, thereby reducing the practicality of the micrometal network structure. Summary of the invention
[0005] In order to solve the technical problem that the surface of the micro-metal network prepared in the prior art is prone to defects and holes, resulting in poor conductivity and light transmittance, the present invention provides a repair method for a micro-metal network structure based on electrochemical deposition.
[0006] The present invention is implemented by the following technical solution: a repair method of a micro-metal network structure based on electrochemical deposition, which comprises the following steps: S1, according to the type of metal in the micro-metal network structure to be repaired, a corresponding electrolyte mixture is prepared, and the prepared electrolyte mixture is placed in an electrochemical deposition device with an electrolytic cell; the electrolyte mixture includes an electrolyte solution, a complexing agent and a buffer; wherein the electrolyte solution uses a substance that can provide ions corresponding to the metal to be deposited in the object to be repaired; the complexing agent uses a substance that can adjust the deposition rate of the electrolyte in the aqueous solution on the micro-metal network structure to be repaired; the buffer is used to adjust the pH value of the electrolyte mixture; S2, setting the polarization potential and repair time of the electrolytic cell according to the type of metal in the micro-metal network structure to be repaired, and placing the pre-treated micro-metal network structure to be repaired in the electrolytic cell for repair; The thickness of the micro-metal network structure to be repaired in the electrolytic cell and the repair time must satisfy the following relationship:
[0007] Wherein, H is the thickness of the micro-metal network structure to be repaired; I is the current; M is the molar mass of the metal in the micro-metal network structure to be repaired; t is the repair time of the micro-metal network structure to be repaired in the electrolytic cell; n is the amount of metal in the micro-metal network structure to be repaired; F is the Faraday constant; A is the surface area of the micro-metal network structure to be repaired; S3, determining whether the micro-metal network structure in the electrolytic cell has been repaired; if so, taking it out of the electrolytic cell, otherwise repeating step S2 to repair it again until the micro-metal network structure is repaired.
[0008] As a further improvement of the present invention, the judgment standard for the completion of repair adopts any one of the following methods: (a) current observation method: by observing the current in the electrolytic cell, when the current in the electrolytic cell changes little and tends to be stable, it indicates that the micrometal network structure to be repaired has been repaired; (b) local conductivity test method: the conductivity of the repaired area in the micrometal network structure is measured by the four-probe method; when the conductivity of the repaired area in the micrometal network structure meets the conductivity requirement after repair, it indicates that the micrometal network structure to be repaired has been repaired; (c) microscope observation method: the repaired micrometal network structure is observed by a scanning electron microscope or an optical microscope. If the repaired micrometal network structure is a continuous and uniform structure, it indicates that the micrometal network structure to be repaired has been repaired.
[0009] The technical solution provided by the present invention has the following beneficial effects: (1) The repair method of the micrometal network structure based on electrochemical deposition provided in the present invention utilizes the principle of electrochemical deposition during the repair process, and can accurately deposit materials at the defects of the micrometal network structure to achieve directional repair, thereby avoiding material waste and unnecessary transmittance loss caused by excessive deposition. The principle of electrochemical deposition is based on the difference in electric field distribution, especially the enhancement effect of the electric field in the defective area of the micrometal network structure. Since the electric field strength is enhanced in areas such as defects, cracks or holes, these areas will become the preferred locations for metal ion deposition during the electrochemical deposition process, thereby promoting the metal ions to preferentially perform reduction deposition in these defective areas, thereby effectively filling the surface defects of the micrometal network structure and achieving effective repair of the micrometal network structure.
[0010] (2) The electrochemical deposition-based repair method for a micrometal network structure provided by the present invention can repair defects in the micrometal network structure while controllably increasing the thickness and width of the metal wires, thereby simultaneously improving the conductivity and transmittance of the repaired micrometal network structure.
[0011] (3) The repair method of the micro-metal network structure based on electrochemical deposition provided by the present invention adopts the principle of electrochemical deposition, so that the repair method can be applied to repair micro-metal network structures of different metal types, thereby improving the applicability of the entire repair method. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a schematic diagram of a repair method for a micro-metal network structure based on electrochemical deposition provided in Example 1 of the present invention.
[0013] Figure 2A curve diagram showing the relationship between repair time and current during repair of a micro-metal network structure repair method based on electrochemical deposition provided in Example 1 of the present invention.
[0014] Figure 3 This is a structural comparison diagram of the micro-metal network structure provided in Example 1 of the present invention before, during and after repair.
[0015] Figure 4 Schematic diagram of the migration of copper ions during the repair of the copper micro-metal network structure by the repair method of the micro-metal network structure based on electrochemical deposition in Example 2 of the present invention.
[0016] Figure 5 This is a picture of the copper micrometal network structure under an electron microscope after being repaired by different electrolyte mixtures when the copper micrometal network structure is repaired in Example 2 of the present invention.
[0017] Figure 6 This is a flow chart of preparing a copper micrometal network structure by a crack template method and performing electrochemical deposition repair in Example 2 of the present invention.
[0018] Figure 7 These are pictures of the copper micrometal network in Example 2 of the present invention before repair and after repair by the repair method of the micrometal network structure based on electrochemical deposition under an optical microscope.
[0019] Figure 8 This is a graph showing the changes in the width and thickness of metal lines in the copper micro-metal network structure during the repair process at different repair times in Example 2 of the present invention.
[0020] Fig. 9 This is a graph showing the changes in the sheet resistance and transmittance of the copper micrometal network structure during the repair process at different repair times in Example 2 of the present invention.
[0021] Fig.10 This is a graph showing the relationship between different repair times and the quality factor of the copper micrometal network structure during the repair process in Example 2 of the present invention.
[0022] Fig.11 These are pictures of the silver micrometal network in Example 2 of the present invention before repair and after repair by the repair method of the micrometal network structure based on electrochemical deposition under an optical microscope. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0024] Example 1 A micrometal network is a nano- or micron-scale network structure composed of metal lines. Metal materials (such as copper, silver, aluminum, etc.) can be deposited in a predetermined area by cracked thin film lithography, wet deposition, magnetron sputtering, etc. to form an interwoven nano- or micron-scale mesh structure. Such metal lines form a highly connected network structure with good electrical conductivity and mechanical properties. In the fields of materials science and electronics, micron metal networks can be made into micrometal network structural parts of various shapes, and the prepared structural parts are widely used in flexible electronics, transparent conductive films, sensors, and electrode materials. The micrometal network structure described in this embodiment is a structural part made by a micrometal network.
[0025] In the study, the applicant also made some comparisons between the micrometal network structure and the metal sheet structure, and obtained the following conclusions: (i) Regarding the conductivity of the two: For the micrometal network structure, since the micrometal network structure is composed of fine metal lines interwoven, its conductivity depends on the connectivity between the metal lines. If the lines in the micrometal network structure are well connected, its conductivity is high; if cracks, breaks or poor connections occur in the micrometal network structure, the conductivity of the micrometal network structure will be significantly affected. However, due to the characteristics of the micron metal network structure itself, when some metal lines in the micrometal network structure are broken, the other parts can still maintain current conduction, which makes the micrometal network structure have better durability when dealing with external pressure, deformation or damage. For metal sheet structures, the conductivity of metal sheet structures depends on the thickness of the metal, the material properties and the surface quality. If the thickness of the metal sheet is large, the conductivity is good. If the thickness of the metal sheet is thin or there are defects on the surface, the conductivity will decrease. And once the metal sheet breaks or cracks, it usually leads to the failure of the entire circuit or structure. (ii) Regarding the transparency of the two: Due to the gaps between the metal lines, the micron or nanometer-scale metal network structure has a high degree of transparency. In the actual preparation process, by optimizing the line width and spacing of the micron metal network, the transparency of the prepared micrometal network structure can be improved. This good transparency makes the metal network particularly suitable for transparent conductive film (TCE), such as touch screens, displays and transparent solar cells. However, because the metal sheet is a continuous metal layer structure, the transmittance of light will be affected by the absorption and reflection of the metal, so the metal sheet usually does not have good transparency. (iii) Regarding the mechanical flexibility of the two: For the micrometal network structure, due to its internal structure of "grid" or "interlaced" characteristics, it usually has good flexibility. Therefore, the micrometal network structure can be bent, stretched or deformed to a certain extent without destroying the structure, making it suitable for flexible electronics and wearable devices. For the metal sheet, because of the whole metal layer, it has a certain rigidity. It is easy to break or be damaged under bending or stress, so the mechanical flexibility of the structure made of metal sheet is worse than that of the micrometal network structure.
[0026] In summary, the micrometal network structure has good conductivity, transparency, mechanical stability, flexibility and scalability. Therefore, it can be widely used in technical fields such as flexible electronic devices, transparent electronic devices, and microwave shielding devices. However, the micrometal network prepared by existing means is prone to defects and holes, which makes it impossible to achieve high transparency, high conductivity and high stability. Therefore, a method is needed to repair the micrometal network structure prepared by the existing technology.
[0027] In this regard, the present embodiment provides a method for repairing a micrometal network structure based on electrochemical deposition, which can repair a micrometal network structure prepared by a preparation method of the prior art. It utilizes the electric field distribution characteristics in electrochemical deposition, especially the tip effect of the electric field, to achieve fixed-point repair of the micrometal network structure. The specific principle is as follows: During the electrochemical deposition process, the electric field will form different distributions on the surface of the working electrode, where areas with stronger electric field strength usually appear at the tip or position with greater curvature on the surface of the working electrode. And metal deposition will occur preferentially at these positions during the electrochemical deposition process. In this embodiment, the micrometal network structure to be repaired is placed in the electrolytic cell as a working electrode. Therefore, the tip or position with greater curvature on the surface of the working electrode corresponds to the area of holes or fractures on the surface of the micrometal network structure. Therefore, the micrometal network structure to be repaired is placed in the electrolytic cell, and under the electric field distribution characteristics, a large amount of metal ions in the electrolyte solution will be driven to preferentially deposit in areas with holes or fractures, thereby achieving the purpose of fixed-point repair of the micrometal network. This kind of fixed-point repair makes the electrochemical deposition process more efficient because it can concentrate the metal ions in the electrolyte solution to a specific repair point, avoiding the need to treat the entire micro-metal network structure during the repair process, saving repair materials while improving repair efficiency. It also avoids large-scale metal deposition during the repair process, which makes the surface of the repaired micro-metal network structure uneven and affects its conductivity.
[0028] A method for repairing a micro-metal network structure based on electrochemical deposition comprises the following steps: S1, according to the type of metal in the micro-metal network structure to be repaired, a corresponding electrolyte mixture is configured, and the configured electrolyte mixture is placed in an electrochemical deposition device with an electrolytic cell. The electrolyte mixture includes an electrolyte solution, a complexing agent and a buffer. The electrolyte solution uses a substance that can provide ions corresponding to the metal required to be deposited in the micro-metal network structure to be repaired. The complexing agent uses a substance that can adjust the deposition rate of metal ions decomposed from electrolyte molecules in an aqueous solution on the micro-metal network structure to be repaired. The buffer is used to adjust the pH value of the electrolyte mixture.
[0029] Since the repair method of the micrometal network structure based on electrochemical deposition in this embodiment can repair micrometal network structures of different metal types. Because micrometal network structures of different metal types have different electrochemical properties, in practical applications, selecting a suitable electrolyte solution to repair the micrometal network structure is a very important process. And the selection of the electrolyte solution is directly related to the efficiency of metal deposition in the electrolytic cell, the repair effect of the micrometal network structure, and the conductivity and stability of the repaired micrometal network structure. Therefore, in the actual repair process, the electrolyte solutions used for the repair of micrometal network structures of different metal types are different. Therefore, before repair, it is necessary to first confirm the metal type of the micrometal network structure to be repaired, and then select a suitable electrolyte solution, and ensure that the metal ions in the selected electrolyte solution match the micrometal network structure to be repaired during the electrochemical deposition process.
[0030] Therefore, before repairing, we will select the corresponding electrolyte solution according to the type of metal in the micrometal network structure to be repaired. The following are the types of electrolyte solutions selected for micrometal network structures with different metal types: (1) If the metal type of the micrometal network structure to be repaired is silver, we can use a silver nitrate solution. In this solution, silver ions exist in a dissolved state in the electrolyte solution. Therefore, by selecting this solution, during the electrochemical deposition process, the silver ions in the silver nitrate solution can be reduced to silver atoms and deposited in the silver micrometal network structure. (2) For the micrometal network structure to be repaired, when the metal type is copper, we can usually use a copper sulfate solution or a copper sulfide solution as the electrolyte solution. The copper ions in these electrolyte solutions can be reduced to copper atoms during the electrochemical deposition process and deposited in the defective areas of the copper micrometal network structure. (3) For the micrometal network structure to be repaired, when the metal type is gold, we can use sodium cyanoaurate (NaAu (CN) 2 ) solution. During the electrochemical reduction process, the gold ions in the gold cyanide solution can be reduced to gold atoms and deposited in the areas that need to be repaired in the micro-metal network structure.
[0031] In addition, in the process of repairing the micrometal network structure by means of electrochemical deposition, the applicant also found that the deposition rate of metal ions in the electrolyte solution, the pH value of the electrolyte solution, etc. will affect the performance of the repaired micrometal network structure. Therefore, in this embodiment, a complexing agent, a buffer and some other additives can be added to the electrolyte solution to optimize the performance of the electrolyte solution and ensure that the electrolyte solution can achieve the best electrochemical deposition effect in the electrolytic cell.
[0032] Among them, with regard to the deposition rate of metal ions in the electrolyte solution, since the deposition rate of metal ions is generally very fast during the electrochemical deposition process, when the micro-metal network structure is repaired by means of electrochemical deposition, it is easy for the surface of the repaired micro-metal network structure to be rough due to excessive or too fast deposition of metal ions in the electrolyte solution, thereby reducing the optical transmittance and conductivity of the repaired micro-metal network structure.
[0033] Therefore, in this embodiment, the deposition rate of metal ions in the electrolyte solution can be adjusted by adding a complexing agent to the electrolyte solution. And the complexing agent needs to be a substance that can adjust the deposition rate of metal ions decomposed from electrolyte molecules in aqueous solution on the micro-metal network structure to be repaired. It mainly forms a stable complex with the metal ions in the electrolyte solution, thereby reducing the concentration of free metal ions in the electrolyte solution, thereby controlling the precipitation rate of metal atoms on the micro-metal network structure. By selecting a complexing agent, the deposition rate of metal ions in the electrolyte solution on the micro-metal network structure that needs to be repaired can be controlled, making the deposition process of metal ions in the electrochemical deposition process smoother and more controllable, thereby achieving uniform deposition of metal ions in the electrolyte solution into the micro-metal network structure that needs to be repaired, avoiding excessive or too fast deposition of metal ions in electrochemical deposition, and improving the conductivity of the repaired micro-metal network structure.
[0034] Because the repair method in this embodiment can repair micro-metallic network structures of different metal types, the complexing agents selected are also different when repairing micro-metallic network structures of different metal types. The selection of complexing agents in this embodiment needs to meet the following conditions: (1) The selected complexing agent must selectively complex the target metal ions in the electrolyte solution (i.e., the metal ions that need to be deposited on the micro-metallic network structure) and avoid forming unstable complexes with other ions in the electrolyte solution to interfere with the deposition process; (2) The complex formed by the selected complexing agent and the metal ions in the electrolyte solution needs to have a high stability constant; (3) When the metal to be deposited is a metal with a high reduction potential, a complexing agent with strong stability needs to be selected to stabilize the metal ions.
[0035] In addition, during the research process, it was found that the pH value of the electrolyte solution will also affect the deposition rate and quality of metal ions. For example, a lower pH value of the electrolyte solution will help the metal ions in the electrolyte solution to undergo reduction deposition, while a higher pH value may slow down the deposition rate of metal ions in the electrolyte solution. Therefore, in the actual repair process, the appropriate pH value is selected for the specific metal type in the micrometal network structure that needs to be repaired, so that the pH value in the electrolyte solution is maintained within the optimal deposition range of the metal ions that need to be deposited, preventing the metal ions from being uneven during the deposition process, and improving the stability and uniformity of the metal ions deposited on the micrometal network structure that needs to be repaired during the electrochemical deposition process.
[0036] It is understandable that in the actual repair process, some additives such as conductive salts can be added to the electrolyte solution according to the metal type of the micrometal network structure to be repaired. The purpose of adding conductive salts is to improve the conductivity of the electrolyte solution and ensure that the current is evenly distributed between the working electrode and the counter electrode, so that the area on the surface of the micrometal network structure that needs to be repaired can obtain a more uniform metal deposition layer, thereby improving the uniformity of the surface of the repaired micrometal network structure and improving the light transmittance and conductivity of the repaired micrometal network structure. In addition, some substances that can inhibit grain growth during electrochemical deposition can also be added.
[0037] S2, setting the polarization potential and repair time of the electrolytic cell according to the type of metal in the micro-metal network structure to be repaired, and placing the pre-treated micro-metal network structure to be repaired in the electrolytic cell for repair.
[0038] Among them, the pretreatment of the micro-metal network structure to be repaired includes the following steps: first, the micro-metal network structure to be repaired is placed in deionized water for ultrasonic cleaning for 10min-50min, and then the micro-metal network structure after ultrasonic cleaning is cleaned with anhydrous ethanol for 5min-10min. Then, the micro-metal network structure after anhydrous ethanol cleaning is blown dry with nitrogen to ensure that the surface of the micron metal network structure to be repaired remains clean, thereby reducing possible impurity contamination during the deposition process. Finally, plasma cleaning is performed, and the plasma cleaning time is 10min and the cleaning power is 40W. In addition, in the actual operation process, in order to improve the adhesion of electrochemical deposition, the surface of the pre-treated micro-metal network structure to be repaired can also be activated with an oxidant (such as dilute nitric acid) before being placed in the electrolytic cell.
[0039] In this embodiment, the micro-metal network structure to be repaired may be ultrasonically cleaned in deionized water for 20 minutes and cleaned in anhydrous ethanol for 10 minutes.
[0040] During the repair process, the electrolyte mixture in the electrolytic cell needs to be continuously stirred, and the stirring process lasts throughout the entire electrochemical deposition process. Continuous stirring of the electrolyte mixture can effectively improve the uniformity of metal ion distribution in the electrolyte solution, thereby improving the uniformity of metal ion deposition on the micro-metal network structure to be repaired.
[0041] In this embodiment, a magnetic stirrer may be used to stir at a speed of 300 rpm-600 rpm, and the stirring time may be 30 min-60 min, so as to ensure that each component in the electrolyte mixture can be uniformly dissolved.
[0042] During the electrochemical deposition process, the electrochemical deposition equipment can use an electrochemical workstation with a three-electrode system. A working electrode, a counter electrode and a reference electrode are provided in the electrolytic cell. The three electrodes in the electrochemical workstation are respectively connected to the working electrode, the counter electrode and the reference electrode in the electrolytic cell. In the present embodiment, a micro-metal network structure is selected as the working electrode, a metal foil with a purity of 99.9% is used as the counter electrode, and an Ag / AgCl electrode is used as a reference electrode. Among them, both the working electrode and the counter electrode can be fixed in the electrolytic cell by a Pt electrode clamp, and when fixed, the Pt sheet in the Pt electrode clamp needs to be in close contact with the micro-metal network structure to be repaired. In addition, the metal type of the metal foil in the counter electrode needs to be the same as the metal type in the micro-metal network structure to be repaired.
[0043] In this embodiment, the working electrode and the counter electrode are fixed in the electrolytic cell by an electrode clamp, and the distance between the working electrode and the counter electrode can be 2 cm to 8 cm. By limiting the distance between the working electrode and the counter electrode, it is possible to ensure that the current between the working electrode and the counter electrode can be evenly distributed, and avoid the occurrence of dendrite growth caused by excessive deposition of metal ions in the electrolyte mixture.
[0044] Preferably, the distance between the working electrode and the counter electrode may be 5 cm.
[0045] When the electrolytic cell is performing electrochemical deposition, the temperature of the electrolyte mixture inside it can be between 25°C and 35°C. It is preferably 30°C. By setting the temperature of the electrolyte mixture to the above temperature range, it can be ensured that the metal ions to be deposited in the electrolyte mixture can achieve the best deposition effect and deposition rate. Among them, the temperature control in the electrolyte mixture can be achieved by a water bath device or a constant temperature heating device. Any of the above devices can maintain the stability of the electrolyte mixture during the deposition process. And in the actual operation process, the change of the current in the electrolytic cell can be recorded every 5 minutes. The deposition parameters in the electrochemical deposition process are adjusted by real-time monitoring of the temperature of the electrolyte mixture and the pH value of the electrolyte mixture to ensure that a uniform metal layer is formed in the area to be repaired on the micrometal network structure to be repaired.
[0046] The working mode of the electrochemical workstation can be selected as constant potential polarization mode. During the electrochemical deposition process, the current density can be 5mA / cm 2 ~20 mA / cm 2 To ensure the compactness and uniformity of the metal ions to be deposited in the electrolyte mixture on the surface of the micro-metal network structure to be repaired. The repair time of electrochemical deposition can be 1min-25min to meet the needs of different repair thicknesses. In the constant potential polarization mode, the electrochemical workstation will display the real-time changes in the current between the working electrode and the counter electrode. Therefore, the progress of the deposition reaction in the electrolytic cell can be observed in real time through the current changes, and it can be judged whether the deposition reaction has achieved the expected effect.
[0047] In this scheme, the thickness of the micro-metal network structure to be repaired in the electrolytic cell and the repair time must satisfy the following relationship:
[0048] Wherein, H is the thickness of the micro-metal network structure to be repaired; I is the current. M is the molar mass of the metal in the micro-metal network structure to be repaired. t is the repair time of the micro-metal network structure to be repaired in the electrolytic cell. n is the amount of metal in the micro-metal network structure to be repaired. F is the Faraday constant. A is the surface area of the micro-metal network structure to be repaired.
[0049] In the above relationship, the type of metal in the micrometal network structure to be repaired is known during repair, that is, the molar mass M of the metal in the micrometal network structure to be repaired, the amount n of the metal in the micrometal network structure to be repaired, and the surface area A of the micrometal network structure to be repaired are also known. And F is the Faraday constant, which represents the amount of charge carried by each mole of electrons. It is a constant, and the specific value is 96485C / mol. Therefore, it can be seen from the above relationship that in the actual repair process, the thickness of the metal ions deposited in the electrolyte mixture on the micrometal network structure to be repaired can be controlled by adjusting the repair time and the current density during the repair process. By controlling the above two quantities, the repair accuracy of the micrometal network structure that needs to be repaired can be improved.
[0050] Among them, for the current density parameter in the electrochemical deposition process, it can directly determine the rate of reduction of metal ions in the electrolyte mixture. A higher current density will increase the reduction rate of metal ions in the electrolyte mixture, thereby accelerating the deposition rate of metal ions in the electrolyte mixture onto the micrometal network structure to be repaired, so within the same repair time, increasing the current density will increase the thickness of the metal layer deposited on the micrometal network structure to be repaired. On the contrary, a smaller current density will result in a slow deposition rate of metal ions in the electrolyte mixture, so that within the same repair time, reducing the current density in the electrolytic cell will cause the thickness of the metal layer deposited on the micrometal network structure to be repaired to become thinner. Therefore, in the actual operation process, we can adjust the current density in the electrolytic cell according to the thickness of the metal layer to be deposited on the micrometal network structure to be repaired. In addition, the higher the current density in the electrolytic cell, the greater the amount of deposition between units deposited on the micrometal network structure to be repaired, so the line thickness and width of the metal layer deposited on the micrometal network structure to be repaired will also increase. The increased line thickness and line width can increase the conductive channels of the repaired micro-metal network structure, thereby significantly improving the conductivity of the repaired micro-metal network structure.
[0051] However, although high current density will accelerate the deposition rate of metal ions in the electrolyte mixture, if the current density in the electrolytic cell is too high, it will also cause uneven deposition of metal ions in the electrolyte mixture, making it easy for rough metal deposition to appear on the surface of the repaired micrometal network structure; it may even form excessive deposition in some areas of the micrometal network structure that needs to be repaired, and incomplete deposition in other areas, which will greatly affect the overall conductivity of the repaired micrometal network structure. Therefore, in actual operation, the current density in the electrolytic cell can be adjusted according to the type of metal of the micrometal network structure that needs to be repaired, the thickness of the deposition, and other repair requirements. In this embodiment, through a series of preliminary experiments, it was found that when the current density in the electrolytic cell was 5mA / cm 2~20mA / cm 2 It can ensure the density and uniformity of the metal ions to be deposited in the electrolyte mixture on the surface of the micro-metal network structure to be repaired.
[0052] As for the repair time, if the repair time is too short, the thickness of the metal ions in the electrolyte mixture deposited on the micro-metal network structure to be repaired will be thin, while other deposition parameters are the same, which may result in incomplete repair. If the repair time is too long, the thickness of the metal ions in the electrolyte mixture deposited on the micro-metal network structure to be repaired will be too thick, resulting in excessive deposition. Therefore, in the actual repair process, the repair time can also be adjusted according to the type of metal of the micro-metal network structure to be repaired, the thickness to be deposited, and other repair requirements. In this embodiment, through a series of preliminary experiments, it was found that when the repair time is set between 1min-25min, it can meet the repair requirements without excessive deposition.
[0053] In addition, when studying the repair time, it was found that the extension of the repair time would increase the amount of metal ions deposited in the electrolyte mixture, thereby increasing the thickness and width of the metal wires deposited in the repair area on the micrometal network structure to be repaired, thereby improving the connectivity and stability of the repaired micrometal network structure. Therefore, in the actual repair process, if the type of repair of the micrometal network structure to be repaired is a case where there are cracks or defects between the metal wires, extending the repair time can help the metal ions in the electrolyte mixture to fill these defects, thereby enhancing the overall stability and conductivity of the repaired micrometal network structure.
[0054] In this embodiment, the electrochemical workstation can also use a pulse potential mode during the electrochemical deposition process to improve the density of the metal ions to be deposited in the electrolyte mixture on the surface of the micro-metal network structure to be repaired. The pulse potential can be set to -0.8V to -1.2V, the pulse time can be 2 seconds, and the interval time is 1 second. By selecting the pulse potential mode, the dendrites formed by the metal ions to be deposited during the deposition process can be effectively reduced, thereby improving the uniformity, light transmittance and conductivity of the repaired micro-metal network structure.
[0055] The electrochemical workstation in this embodiment includes an electrolytic cell, such as Figure 1As shown, the electrolytic cell is filled with an electrolyte mixture, and the electrolyte mixture contains many metal ions of the same metal type as the micrometal network structure that needs to be repaired. In this device, the micrometal network structure to be repaired serves as the working electrode, and the high-purity metal foil serves as the counter electrode. The working electrode and the counter electrode are respectively connected to an external power supply through wires, thereby forming a complete electrochemical circuit. In this electrochemical circuit, the working electrode (that is, the micrometal network structure to be repaired) has a negative potential, which is usually between -0.1V and -1.2V. The counter electrode has a positive potential. Therefore, a strong electric field is formed between the working electrode and the counter electrode. Since the potential of the working electrode is set to a negative value, the metal ions ( Figure 1 The blue sphere in the middle will move from the counter electrode to the surface of the working electrode under the drive of the electric field, and receive electrons ( Figure 1 Medium white ball - ) and undergo a reduction reaction to generate metal atoms. And in the process of electrochemical deposition, the area where the metal ions are selectively deposited is affected by the charge density on the surface of the working electrode. In the micrometal network structure to be repaired, the electric field strength of the areas that need to be repaired, such as the fracture position, hole position and gap position, is usually relatively high. The reason why the electric field strength in these areas is relatively high is that the radius of curvature of these areas is small and the charge density is large, so these positions will preferentially attract metal ions in the electrolyte mixture, so that the metal ions in the electrolyte mixture will be preferentially deposited in these areas, thereby gradually filling the cracks and holes in the defects of the micrometal network structure and realizing the fixed-point repair of the micrometal network structure. To restore the continuity and conductivity of the micrometal network structure. At the same time, the line thickness and line width of the repaired micrometal network structure will also increase, which can greatly improve the conductivity and quality factor of the repaired micrometal network structure.
[0056] Among them, the quality factor (Figure of Merit, referred to as FOM) is a comprehensive indicator for evaluating optoelectronic performance. It is widely used to describe the performance of transparent conductive materials. The quality factor usually combines the conductivity and light transmittance of the material to provide a unified measurement standard for the performance of the material in practical applications. It combines the two performance parameters of conductivity and light transmittance to give an evaluation of the comprehensive performance of the material. The calculation formula of the quality factor FOM is:
[0057] Wherein, T is the transmittance of the repaired micro-metal network structure, and Rs is the sheet resistance of the repaired micro-metal network structure.
[0058] Sheet resistance, also known as film resistance, is a measurement value used to indirectly characterize the thermal infrared performance of vacuum coatings on samples such as thin film layers and glass coating layers. The value can be directly converted into thermal infrared emissivity. For a micrometal network structure, the smaller its Rs is, the better the conductivity of the micrometal network structure is, and the smaller the resistance of current passing through the micrometal network structure is. The larger T is, the stronger the micrometal network structure's ability to transmit visible light is, and the more transparent it is. In the quality factor formula, the smaller Rs is, the larger T is, and the larger the quality factor (FOM) is. Therefore, if the quality factor (FOM) of the micrometal network structure is larger, it means that the micrometal network structure has both high transmittance and high conductivity.
[0059] In this embodiment, the quality factor of the micro-metal network structure is obtained by measuring the sheet resistance and transmittance of the micro-metal network structure at different repair times.
[0060] S3, determining whether the micro-metal network structure in the electrolytic cell has been repaired; if the repair is completed, taking the repaired micro-metal network structure out of the electrochemical precipitation tank; if the repair is not completed, repeating step S2 to repair it again until the micro-metal network structure is repaired.
[0061] Among them, in step S3, any of the following methods can be used to determine whether the micrometal network structure in the electrolytic cell has been repaired: (i) Current observation method: In this method, the current change between the working electrode and the counter electrode on the electrochemical workstation can be directly observed to determine whether the deposition has achieved the expected effect. The reason is that when the micrometal network structure is not repaired, there are many broken areas and hole areas on its surface, which leads to poor conductivity of the unrepaired micrometal network structure. Therefore, in the early stage of electrochemical deposition of the micrometal network structure that needs to be repaired, please refer to Figure 2As shown, the current between the working electrode and the counter electrode will be very small. As the repair process proceeds, the fractured areas and hole areas on the surface of the micrometal network structure to be repaired are fully repaired and filled. At this time, the conductivity of the micrometal network structure in the electrolytic cell is greatly improved, so the current between the working electrode and the counter electrode will gradually increase. Therefore, in this judgment method, when the current between the working electrode and the counter electrode on the electrochemical workstation changes greatly, it means that the electrochemical workstation is undergoing a repair operation at this time. When the change in the current between the working electrode and the counter electrode is small and tends to be stable, it means that the defects on the surface of the micrometal network structure in the electrolytic cell have been effectively repaired. (II) Local conductivity test method: This method can measure the conductivity of the repaired area in the repaired micrometal network structure by the four-probe method to determine whether the micrometal network structure has been repaired. Among them, conductivity is the reciprocal of resistance. The principle is: during the repair process, the defective area in the micrometal network structure usually increases the resistance, while the conductivity of the repaired micrometal network structure will be improved. Therefore, in the actual measurement process, the resistance of the area to be repaired in the micrometal network structure can be measured to make a judgment. If the resistance of the area to be repaired in the repaired micrometal network structure drops significantly, the surface of the area has been repaired. (III) Microscope observation method: This method can observe the surface of the repaired micrometal network structure through a scanning electron microscope (SEM) or an optical microscope. If the repaired micrometal network structure is a continuous and uniform structure, it indicates that the micrometal network structure to be repaired has been repaired. In this judgment method, a scanning electron microscope can be used for metal network structural parts at the micron level, because the scanning electron microscope can provide higher resolution surface images, which can help judge the repair effect of the micrometal network structure.
[0062] For the above three judgment methods, the current observation method can be directly judged during the repair process. The local conductivity test method and the microscope observation method both require the repaired micrometal network structure to be removed from the electrolytic cell before judgment can be made. In actual use, any of the above methods can be used to determine whether the micrometal network structure has been repaired, or any combination of two or more methods can be used to determine whether the micrometal network structure has been repaired. For example, the current method and the microscope observation method can be combined to determine whether the micrometal network structure has been repaired. In the above judgment method, if the judgment process requires the repaired micrometal network structure to be removed from the electrolytic cell, the electrochemical workstation can be suspended at this time, and the repaired micrometal network structure can be removed from the electrolytic cell, and then the repair effect of the removed micrometal network structure can be judged by the microscope observation method or the local conductivity test method. If the repair is completed, the entire electrochemical deposition process can be stopped. If the repair is not completed, the repaired micrometal network structure can be pre-treated and then placed in the electrolytic cell, and the electrochemical workstation can be started again until the repair of the micrometal network structure achieves the expected effect.
[0063] The repair standard of the micrometal network structure can also be determined by measuring the sheet resistance of the repaired micrometal network structure. If the sheet resistance of the repaired micrometal network structure is less than 1Ω / sq, it means that the repair of the micrometal network structure meets the requirements.
[0064] In this embodiment, the above-mentioned repair method can be used to repair a micro-metal network structure in which the metal type in the micro-metal network structure is any single metal such as gold, silver, aluminum, copper, platinum, nickel, titanium, etc.
[0065] Among them, the process of repairing the micro-metal network structure can be referred to Figure 3 shown. Figure 3 Shows the changes in the micro-metal network structure before, during and after restoration.
[0066] The repair method of this embodiment is applicable to micro-metal network structures prepared by photolithography, PS ball template method, crack template method and solution self-assembled nanowire method in the prior art.
[0067] The present invention provides a process for defect repair and performance optimization of micrometal network structures represented by cracked thin film lithography methods using electrochemical deposition technology. This method can effectively solve the problem of metal network structure defects caused by factors such as residual particles in the template, incomplete cracking or mechanical stress, and significantly improve the optoelectronic performance and structural stability of micrometal networks in the fields of transparent conductive electrodes, flexible sensors and wearable devices.
[0068] The present invention realizes the fixed-point repair of the metal network structure by utilizing the tip effect of the electric field distribution. And significantly improves the conductivity of the metal network through the electrochemical deposition process. The method can accurately repair local defects in the metal network, improve the uniformity and conductivity of the overall network structure, and provide a new technical solution for the preparation of metal networks with high optoelectronic performance.
[0069] The technical solution of the present invention provides an effective repair method for solving the defect problem of metal network structural parts during the preparation process, and further optimizes the performance of metal network structural parts. Compared with the traditional preparation and repair method of micro-metal network structure, the present invention has the following advantages: First, the electrochemical deposition process can accurately deposit materials at the defects of the metal network to achieve directional repair, avoiding material waste and unnecessary transmittance loss caused by excessive deposition. Among them, the principle of electrochemical deposition is based on the difference in electric field distribution, especially the enhancement effect of electric field in defective areas in metal networks. Due to the local enhancement of electric field at defects, cracks or holes, these areas will become the priority positions for metal ion deposition. Promote the reduction deposition of metal in defective areas, thereby effectively filling the surface defects of micro-metal networks. Secondly, with the assistance of electrochemical methods, the thickness and width of the metal wires of the micro-metal network structure can be controllably increased during the repair process, thereby achieving an optimized balance between high conductivity and transmittance. This repair and optimization technology is of great significance in improving the optoelectronic quality factor of micro-metal network structures, and provides an efficient and feasible solution for preparing high-performance flexible transparent electrodes. In summary, the repair and optimization scheme proposed in the present invention not only overcomes the defects of the existing crack thin film lithography technology, but also can significantly improve the optoelectronic properties of the micro-metal network structure, and has broad application prospects and important practical value.
[0070] Example 2 This embodiment provides a specific process for repairing a copper micro-metallic network structure through the general repair method of the micro-metallic network structure based on electrochemical deposition in Example 1.
[0071] In addition, you can Figure 4 To show the migration of copper ions during the repair of the copper micrometallic network structure. Figure 4 The black horizontal line represents the negative charge carried by the copper metal network structure. Figure 4 The middle left picture shows how copper ions are reduced to copper atoms due to the tip effect and continue to grow along the broken part of the network during electrochemical deposition. The right picture shows how copper ions are reduced to copper atoms and fill the hole area of the metal network.
[0072] A method for repairing a copper micrometal network structure based on electrochemical deposition comprises the following steps: S1, pretreatment: the copper micrometal network structure prepared by the crack template method is ultrasonically cleaned with deionized water, and then cleaned with anhydrous ethanol for 10 minutes, and the copper micrometal network structure after the anhydrous ethanol cleaning is blown dry with nitrogen; finally, plasma cleaning is performed, the plasma cleaning time is 10 minutes, and the cleaning power is 40W.
[0073] S2, prepare an electrolyte mixture suitable for repairing the copper micrometallic network structure, pour the prepared electrolyte mixture into the electrolytic cell. And continuously stir the electrolyte mixture in the electrolytic cell by a magnetic stirrer. The electrolyte mixture includes CuSO 4 ·5H 2 O、Na 4 P 2 O 7 10H 2 O、NaHPO 4 12H 2 O, polyethylene glycol (PEG-600), and thiourea.
[0074] S3, setting the polarization potential and repair time of the electrolytic cell according to the type of metal in the micro-metal network structure to be repaired, and placing the pretreated micro-metal network structure to be repaired in the electrolytic cell for repair; The thickness of the micro-metal network structure to be repaired in the electrolytic cell and the repair time must satisfy the following relationship:
[0075] Among them, H is the thickness of the micrometal network structure to be repaired; I is the current; M is the molar mass of the metal in the micrometal network structure to be repaired; t is the repair time of the micrometal network structure to be repaired in the electrolytic cell; n is the amount of metal in the micrometal network structure to be repaired; F is the Faraday constant; A is the surface area of the micrometal network structure to be repaired.
[0076] S4, determining whether the micro-metal network structure in the electrolytic cell has been repaired; if so, taking the repaired micro-metal network structure out of the electrolytic cell; otherwise, repeating step S3 to repair it again until the micro-metal network structure is repaired.
[0077] In this embodiment, the electrolyte mixture and repair conditions of the micro-metal network structure with copper as the metal type during the repair process are also studied. The details are as follows: Since the metal type of the micro-metal network structure to be repaired is copper, the electrolyte mixture may contain CuSO 4 ·5H 2 O、Na 4 P2 O 7 10H 2 O、Na 2 HPO 4 12H 2 O、NH 4 NO 3 , polyethylene glycol, thiourea. Among them, CuSO 4 ·5H 2 O as electrolyte solution, Na 4 P 2 O 7 10H 2 O as complexing agent, Na 2 HPO 4 12H 2 O as a buffer, NH 4 NO 3 As conductive salt. Polyethylene glycol and thiourea as other additives.
[0078] Among them, Na 4 P 2 O 7 10H 2 The reason why sodium pyrophosphate is used as a complexing agent is that Na 4 P 2 O 7 10H 2 O can react with Cu 2+ The complex with high stability constant is formed, which can stabilize copper ions in the electrochemical deposition process and prevent the surface roughness of the repaired copper micrometallic network structure caused by excessive copper ion deposition. 4 P 2 O 7 10H 2 O can also play a role in adjusting the pH value of the electrolyte mixture and maintaining the stability of the electrolyte mixture. 2 HPO 4 12H 2 O serves as a buffer to 2 HPO 4 12H 2 O can effectively stabilize the pH value of the solution. 4 P 2 O 7 10H 2 O can maintain the pH value of the electrolyte mixture within a range suitable for copper ion deposition, thereby avoiding the phenomenon of uneven copper ion deposition during the deposition process. 4 NO 3As a conductive salt, it can improve the conductivity of the electrolyte mixture and ensure that the current can be evenly distributed between the working electrode and the counter electrode, so that a more uniform copper precipitation layer can be obtained on the micrometallic network copper structure, thereby improving the conductivity of the repaired copper micrometallic network structure. Polyethylene glycol, as an additive, can improve deposition uniformity and reduce deposition defects. At the same time, PEG-6000 can adjust the viscosity of the solution and reduce the surface tension during the electrochemical deposition process, which helps to form a uniform metal copper deposition layer and reduce the growth of dendrites, thereby improving the quality and conductivity of the repaired copper micrometallic network structure. Thiourea can be added during the electrochemical deposition process, which can inhibit the growth of grains and make the deposited metal layer denser and smoother. In addition, in the setting of the working electrode, the area of the working electrode can be increased to reduce the local current density and thus improve the uniformity of deposition.
[0079] We prefer CuSO 4 ·5H 2 O as the electrolyte solution. It can provide the Cu required in the electrochemical deposition process 2+ ions. 4 ·5H 2 O as the electrolyte solution, the applicant also studied CuSO 4 ·5H 2 O was studied. During the research, the applicant found through a series of experiments that in 100 mL of deionized water, if CuSO 4 ·5H 2 When the concentration of CuSO4 is lower than 0.15 g / L, the copper ions in the prepared electrolyte mixture will not be able to meet the deposition requirements, resulting in uneven copper deposition on the copper micrometallic network structure after electrochemical deposition repair, thus affecting its repair effect and conductive properties. 4 ·5H 2 When the concentration of CuSO4 is higher than 0.2 g / L, although the prepared electrolyte mixture can provide enough copper ions, the concentration of copper ions in the electrolyte mixture is too high, which leads to excessive formation of dendrites when depositing the copper micrometallic network structure by electrochemical deposition, resulting in the rough surface of the repaired copper micrometallic network structure, thereby reducing the light transmittance and conductivity of the repaired copper micrometallic network structure. Therefore, when repairing the copper micrometallic network structure, if CuSO4 is used, 4 ·5H 2 O is used as the source of copper ions, then CuSO 4 ·5H 2 The concentration range of O is between 0.15g / L and 0.2g / L.
[0080] In addition, the applicant also analyzed the amount of several substances remaining in the electrolyte mixture and obtained the following conclusions: When depositing the copper micrometallic network structure, Na 4 P 2 O 7 10H 2 The concentration of O can be 0.55 gg / L ~ 0.70 g / L; Na 2 HPO 4 12H 2 The concentration of O can be 0.15g / L~0.2g / L; NH 4 NO 3 The concentration of can be 0.025g / L ~ 0.035g / L; the concentration of polyethylene glycol is 0.01g / L ~ 0.1g / L; the concentration of thiourea is 0.01g / L ~ 0.05g / L.
[0081] Furthermore, Na 4 P 2 O 7 10H 2 The concentration of O can be 0.6 g / L, 0.625 g / L, and 0.65 g / L. 2 HPO 4 12H 2 The concentration of O can be 0.155 g / L, 0.158 g / L, and 0.16 g / L. 4 NO 3 The concentration of can be 0.028 g / L, 0.03 g / L, 0.032 g / L. The concentration of polyethylene glycol is 0.05 g / L. The concentration of thiourea is 0.03 g / L.
[0082] The prepared electrolyte mixture can be stored in a dark environment to prevent oxidative decomposition of copper ions in the electrolyte mixture.
[0083] Furthermore, the applicant has also studied and configured three different electrolyte mixtures to study the repair effects of different electrolyte mixtures on the copper micrometallic network structure. The first electrolyte mixture is composed of CuSO 4 ·5H 2 O and deionized water; the second electrolyte mixture is composed of CuSO 4 ·5H 2 O、Na 4 P 2 O 7 10H 2 O and deionized water; and the third electrolyte mixture is composed of CuSO 4 ·5H 2 O、Na 4 P2 O 7 10H 2 O、Na 2 HPO 4 12H 2 O and deionized water.
[0084] Through the above electrochemical deposition repair method, during the electrochemical deposition repair process, other parameters remain the same, and only the type of electrolyte mixture is changed. By selecting these three different electrolyte mixtures to repair the copper micrometal network structure, and placing the repaired copper micrometal network structure under an electron microscope for observation, the following results are obtained: Figure 5 result.
[0085] in, Figure 5 (1) is a picture of the copper micrometal network structure repaired by the first electrolyte mixture under an electron microscope; Figure 5 (2) is a picture of the copper micro-metal network structure repaired by the second electrolyte mixture under an electron microscope; Figure 5 (3) is a picture of the copper micro-metal network structure repaired by the third electrolyte mixture under an electron microscope. Figure 5 Comparing the three pictures in the figure, it can be seen that when repairing the copper micrometallic network structure, if the electrolyte mixture is simply an electrolyte solution that can provide the metal ions that need to be deposited, its repair effect is relatively poor. If the electrolyte mixture is a mixture of an electrolyte solution that can provide the metal ions that need to be deposited and a complexing agent, its repair effect is better than the repair effect of only a simple electrolyte solution. This proves that adding a suitable complexing agent to the electrolyte mixture can improve the repair effect of the micrometallic copper network by means of electrochemical deposition. If the electrolyte mixture is a mixture of an electrolyte solution that can provide the metal ions that need to be deposited, a complexing agent and a buffer, its repair effect is better than the repair effect of an electrolyte solution that can provide the metal ions that need to be deposited and a complexing agent. This proves that adding a suitable buffer to the electrolyte mixture can also improve the repair effect of the micrometallic copper network by means of electrochemical deposition.
[0086] The copper micro-metal network structure in this embodiment can be prepared by the crack template method in the prior art. The specific preparation process of the copper micro-metal network structure prepared by the crack template method is described below. Figure 6 shown, and in Figure 6 The last step is to repair the copper micrometal network structure prepared by the crack template method by electrochemical deposition to obtain the repaired copper micrometal network structure.
[0087] A method for preparing a copper micrometal network structure, the preparation process can refer to Figure 6 As shown, it includes the following steps: S1: Prepare a crack network template on a substrate.
[0088] Nano-sized titanium dioxide particles are mixed with a certain amount of ethanol solution to form a crack colloid solution, and the concentration of the solution can be adjusted according to specific conditions. The uniformly mixed crack colloid solution is dripped onto the surface of the substrate and dried in a vacuum to produce a regular rectangular crack network template.
[0089] S2: Depositing a metal copper film on the template surface by DC magnetron sputtering.
[0090] The crack network template is placed in a vacuum chamber for magnetron sputtering coating. Metal copper atoms will gradually deposit into the cracks of the template, thereby forming a metal copper film on the surface of the crack template.
[0091] S3: Remove the template to obtain a copper micro-metal network structure.
[0092] The crack template sample with a metal copper film after magnetron sputtering is placed in an ethanol solution for ultrasonic treatment. The crack template will quickly dissolve in the ethanol after ultrasonic treatment, leaving only the metal copper deposited in the crack network on the surface of the substrate, thereby obtaining a copper micro-metal network structure.
[0093] The crack colloid solution selected in step S1 can be a commercial titanium dioxide (P25) nanoparticle colloid solution, a titanium dioxide solution, an aqueous acrylic resin solution, an egg white solution, a polymer sol-gel CA600 solution, a sodium carbonate solution, a SiO 2 Any one of a nanoparticle solution and an aqueous polystyrene nanoparticle suspension, or a mixture of any two or more of them.
[0094] In this embodiment, we use a colloidal solution with commercial nano-sized titanium dioxide as the solute and anhydrous ethanol as the solvent as the precursor solution for generating the crack template. The particle size of the commercial nano-sized titanium dioxide particles can range from 20nm to 100nm, and the characteristic size of the generated crack network can be adjusted by selecting titanium dioxide particles in this range.
[0095] Furthermore, when the particle size of the titanium dioxide nanoparticles is 50 nm, a uniform crack network film can be obtained through step S1.
[0096] When preparing the crack colloid solution in step S1, the nano titanium dioxide particles and the ethanol solution can be mixed by magnetic stirring. The stirring time can be 30 minutes to 60 minutes. In addition, a plastic wrap is required to be sealed on the surface of the beaker during stirring to slow down the evaporation of the solvent during the stirring process.
[0097] Furthermore, the stirring time of step S1 may be 45 minutes, under which the prepared crack colloid solution can be ensured to be mixed evenly to obtain the best crack effect.
[0098] The width of the crack network film obtained by step S1 is 2 μm-10 μm. The value of the width of the crack network film obtained depends on the concentration of the obtained crack colloid solution and the drying speed. In this embodiment, the concentration of the crack colloid solution obtained by nano-sized titanium dioxide particles and ethanol solution is 0.08 g / mL~0.16 g / mL. The temperature range during the drying process is 20°C~80°C.
[0099] In this embodiment, when the crack colloid solution prepared in step S1 is dripped onto the surface of the substrate, the dripping amount of the crack colloid solution per square centimeter on the substrate may range from 10 μL to 60 μL.
[0100] In step S2, when depositing the metal copper film, the temperature in the vacuum chamber is controlled between 20°C and 40°C. By setting this range, the generation of internal stress in the metal copper film can be reduced. If the temperature in the vacuum chamber is too high, the sputtered metal copper may be oxidized, causing the obtained metal copper film to lose its good conductivity. During the DC sputtering process, the sputtering time can be 20min~60min to meet the needs of obtaining metal copper films of different thicknesses. Argon gas can be used as the sputtering gas, and the flow rate is controlled between 10sccm-30sccm to ensure that the metal copper atoms can be evenly deposited in the cracks of the template. The sputtering power of the power supply during magnetron sputtering can be between 30W-100W.
[0101] Furthermore, the temperature in the vacuum chamber may be 25° C.; the sputtering time may be 30 min; the flow rate of the introduced argon gas may be 15 sccm; and the sputtering power of the power supply during the magnetron sputtering process may be 50 W.
[0102] In step S3, the temperature of the ultrasonic treatment may be between 20°C and 40°C. Within this temperature range, the oxidation of the metal copper film can be accelerated while also accelerating the dissolution rate of the titanium dioxide crack template.
[0103] After the copper micrometal network structure is obtained by the above method, its surface is cleaned with deionized water, and at the same time, a plasma cleaner is used to remove impurities on the surface of the copper micrometal network structure to improve the surface energy of the copper micrometal network structure. The cleaned micrometal network structure can be dried in a vacuum drying oven for 5min-10min to remove excess deionized water during the cleaning process. After the dried micrometal network structure is observed by a scanning electron microscope, it is found that there are a large number of hole areas, fracture areas and discontinuous areas on the surface of the copper micrometal network structure prepared by the crack template method. And by measuring the square resistance of the obtained copper micrometal network structure, it can be seen that its square resistance is very large and its conductivity is very poor. Therefore, a repair process is needed to repair the copper micrometal network structure prepared by the crack template method.
[0104] In the process of using a plasma machine for cleaning, the power of the plasma machine is set to 40W-100W, and the time is 3min-10min.
[0105] The following is a specific process for preparing a copper micrometallic network structure by the crack template method: first, dissolve 1.2 g of titanium dioxide powder in 10 mL of anhydrous ethanol, cover the top of the beaker with plastic wrap to prevent rapid evaporation of the solvent during stirring, and add 0.3 g of PVA powder to increase the adhesion of the crack colloid solution. Place the solution in an ultrasonic cleaner for ultrasonic dispersion treatment, and finally place it in a magnetic stirrer for stirring until the titanium dioxide is fully dissolved for use. After that, the substrate is cleaned with ethanol, deionized water, and acetone several times and fixed on a smooth acrylic plate. The prepared crack colloid solution is stirred at 30 μL / cm 2 The dosage was evenly dropped on the substrate surface. The substrate was moved into a vacuum drying oven and vacuum dried at 60 °C, and finally a uniform crack network template was produced. The obtained template was deposited with copper thin film, the sputtering pressure was 0.73 Pa, the argon flow rate was 14 sccm, and the sputtering power was 80 W. After sputtering for 1 hour, the sample was taken out and ultrasonically treated in anhydrous ethanol, and the template was removed to obtain a copper micrometal network structure.
[0106] The copper micro-metal network structure obtained by the crack template method is repaired by the following specific repair process. The specific repair process is as follows: A method for repairing a copper micrometal network structure based on electrochemical deposition comprises the following steps: S1, pretreatment: the copper micrometal network structure prepared by the crack template method is ultrasonically cleaned with deionized water, and then cleaned with anhydrous ethanol for 10 minutes, and the copper micrometal network structure after being cleaned with anhydrous ethanol is blown dry with nitrogen.
[0107] S2, prepare electrolyte mixture: 1.58g CuSO 4 ·5H 2 O was added to 100 mL of deionized water, and then 6.25 g of Na 4 P 2 O 7 10H 2 O, 1.58 g NaHPO 4 12H 2 O, 0.3 g NH 4 NO 3 As well as 0.05g of polyethylene glycol (PEG-600) and 0.03g / L of thiourea. Stir these components to fully dissolve them in deionized water, and finally obtain a blue transparent electrolyte mixture. Pour the prepared electrolyte mixture into the electrolytic cell. And continue to stir the electrolyte mixture in the electrolytic cell with a magnetic stirrer.
[0108] S3, repair: Use an electrochemical workstation with a three-electrode system, and connect the three electrodes in the electrochemical workstation to the working electrode, the reference electrode, and the counter electrode, respectively. Then use the copper micrometal network structure to be repaired as the working electrode and fix it in the electrolytic cell through a Pt electrode clamp. The counter electrode also uses a copper foil with a purity of 99.9%, and the copper foil is also fixed in the electrolytic cell through a Pt electrode clamp. The distance between the copper micrometal network structure to be repaired and the copper foil is 5 cm. The temperature of the electrolyte is maintained at 30°C, and the electrochemical workstation is set to a constant potential polarization mode, and the potential in the constant potential polarization mode is -0.2V for deposition reaction. After the deposition is completed, the electrolyte on the surface of the repaired copper micrometal network structure is cleaned to obtain the repaired copper micrometal network structure.
[0109] In addition, this embodiment also lists a repair process for repairing the silver micrometal network structure prepared by the existing crack template method, and the specific repair operation is as follows: S1, pretreatment: the silver micrometal network structure prepared by the crack template method is ultrasonically cleaned with deionized water, and then cleaned with anhydrous ethanol for 10 minutes, and the silver micrometal network structure after cleaning with anhydrous ethanol is blown dry with nitrogen.
[0110] S2, prepare electrolyte mixture: 5gAgNO 3 Add 100 mL of deionized water and then add 23.0 g of Na 2 S 2 O 3 5g KHSO 3The components are stirred to fully dissolve in deionized water to obtain an electrolyte mixture. The prepared electrolyte mixture is poured into an electrolytic cell. The electrolyte mixture in the electrolytic cell is continuously stirred by a magnetic stirrer.
[0111] Among them, AgNO 3 It can be used as the main source of metallic silver in the electrochemical deposition process, providing silver ions to the silver micro-metallic network structure that needs to be repaired. 2 S 2 O 3 It can be used as a complexing agent to form silver complexes (such as Ag(S 2 O 3 ) 2 3- ) This complex can reduce the precipitation rate of silver, thereby avoiding the appearance of uneven or rough silver deposition layers in the silver micrometallic network structure during electrochemical deposition. 2 S 2 O 3 It also helps maintain stability and uniformity during electrochemical deposition. KHSO 3 It can be used as a reducing agent to provide reducing substances in the electrochemical deposition process, which can directly or indirectly react with the formed silver complex to release silver atoms, thereby improving the deposition efficiency of the electrochemical deposition process. 3 It can also buffer the pH value of the solution, further stabilize the electrochemical deposition system, and promote the reduction deposition of silver ions.
[0112] S3, repair: Use an electrochemical workstation with a three-electrode system, and connect the three electrodes in the electrochemical workstation to the working electrode, the reference electrode, and the counter electrode respectively. Then use the silver micrometal network structure to be repaired as the working electrode and fix it in the electrolytic cell through a Pt electrode clamp. The counter electrode also uses a silver foil with a purity of 99.9%, and the silver foil is also fixed in the electrolytic cell through a Pt electrode clamp. The distance between the silver micrometal network structure to be repaired and the silver foil is 5cm. The temperature of the electrolyte is maintained at 30°C, and the electrochemical workstation is set to a constant potential polarization mode, and the potential in the constant potential polarization mode is -0.2V for deposition reaction. After the deposition is completed, the electrolyte on the surface of the repaired silver micrometal network structure is cleaned to obtain the repaired silver micrometal network structure.
[0113] Performance Comparison 1. Comparison of some properties of the copper micrometal network structure before and after repair (1.1) Optical microscope The copper metal network structure samples before repair and the copper micro-metal network structure samples after repair were observed under an optical microscope respectively. Figure 7 The picture shown. Figure 7 The middle left picture is an optical microscope image of the copper micrometal network structure before repair. Figure 7 The middle right picture is an optical microscope image of the copper micro-metal network structure after being repaired by electrochemical deposition. Figure 7 From the analysis of the middle left figure, we can see that Figure 7 The area marked by red circles in the middle left image clearly shows multiple defects in the copper micrometal network structure before repair. These defects include obvious cracks (such as the breakage of some metal lines in the picture) and holes. Because of these defects, the structure of the prepared copper micrometal network structure is discontinuous. At multiple intersections or weak areas of multiple copper micrometal network structures, cracks appear as obvious breaks in metal lines, and the hole areas show metal shedding or insufficient deposition during the preparation process. The presence of these factors directly leads to an increase in the resistance of the prepared copper micrometal network structure and a decrease in overall conductivity. As for Figure 7 From the analysis of the middle right figure, we can see that Figure 7 The area marked with red circles in the middle right figure clearly shows that the cracks and holes in the prepared copper micrometallic network structure are effectively filled by the repair method of this embodiment. After being repaired by the electrochemical deposition method of this embodiment, a continuous and dense metal layer has been formed at the original holes and cracks, which significantly improves the integrity of the micrometallic copper network structure. The defective areas at the intersections are also evenly covered with copper by electrochemical deposition, and there are no obvious fractures and holes. This proves that the repair method of this embodiment can achieve fixed-point repair and improve the accuracy of the repair process. In addition, Figure 7 The surface of the copper micrometal network structure in the middle right image is smoother and more uniform, and shows higher continuity in the area marked by the red circle, which proves that the repair method of this embodiment can effectively repair the copper micrometal network structure.
[0114] (1.2) The applicant also studied the changing trend of the metal line width and thickness of the repaired copper micro-metal network structure at different repair times. The width and thickness of the metal wires were measured by scanning electron microscopy. During the repair process, the width and thickness of the metal wires of the copper micrometal network structure were measured at different repair times. Figure 8 . Figure 8 This is a diagram showing the changes in the width and thickness of the metal lines in the copper micro-metal network structure during the repair process at different repair times. Figure 8 The red line in the middle shows the changes in the width of the metal lines in the micro-metal network structure with different repair times. Figure 8The blue line in the middle shows the changes in the thickness of the metal lines in the micro-metal network structure with different repair times. Figure 8 It can be seen that within the same repair time, the growth rate of the width of the metal line during the electrochemical deposition process is faster than the growth rate of the thickness of the metal line, which indicates that in the electrochemical deposition repair method of this embodiment, the metal ions in the electrolyte mixture are more inclined to expand laterally.
[0115] (1.3) The applicant also studied the changing trends of block resistance and transmittance of the repaired copper micrometal network structure at different repair times. Transmittance (T) is a physical term that indicates the ability of light to pass through a medium. It is the percentage of the luminous flux passing through a transparent or translucent body to the incident luminous flux. It can be measured by a UV-visible light photometer. In this embodiment, the transmittance of the copper micrometal network structure is its light transmittance at a wavelength of 550nm.
[0116] Sheet resistance (Rs), also known as film resistance, is a measurement value used to indirectly characterize the thermal infrared performance of vacuum coatings on samples such as thin film layers and glass coating layers. This value can be directly converted into thermal infrared emissivity. For a micrometal network structure, the smaller its Rs is, the better the conductivity of the micrometal network structure is, and the smaller the resistance of current passing through the micrometal network structure is. The larger T is, the stronger the micrometal network structure's ability to transmit visible light is, and the more transparent it is. In this embodiment, the sheet resistance of the copper micrometal network structure can be measured by a four-probe resistance tester.
[0117] During the repair process, the square resistance and transmittance of the copper micrometal network structure were measured at different repair times. Fig. 9 .
[0118] Fig. 9 This is a graph showing the changes in sheet resistance and transmittance of the copper micrometal network structure during the repair process at different repair times. Fig. 9 The red line in the middle represents the curve of the change in the sheet resistance of the micro-metal network structure at different repair times. Figure 8 The blue line in the middle shows the curve of the change of light transmittance of the micro-metal network structure at different repair times. Fig. 9It can be seen that with the increase of repair time, the sheet resistance of the copper micrometal network structure will decrease significantly with the increase of repair time. After decreasing to a certain value, the sheet resistance of the copper micrometal network structure will decrease very slowly and tend to be stable as the repair time increases further. And the repair time corresponding to the significant decrease of the sheet resistance is between 0min-5min, which indicates that in the early stage of electrochemical deposition, the defects in the copper micrometal network structure are quickly repaired, making the current path of the repaired copper micrometal network structure more continuous, thereby causing the sheet resistance of the repaired copper micrometal network structure to decrease rapidly. As the repair time increases further, the decrease of the sheet resistance becomes slow and tends to be stable, which shows that most of the defects in the copper micrometal network structure to be repaired have been repaired at this time, and the repair of electrochemical deposition has reached saturation, so that the gain effect brought by electrochemical deposition is gradually weakened. At the same time, with the increase of repair time, the transmittance gradually decreases, and the decline rate is relatively slow in the early deposition stage, and becomes more obvious in the later stage of deposition. The decrease in transmittance in the later stage of deposition is mainly due to the increase in the width of the metal lines covering more light channels, especially when the deposition time is longer, the light blocking effect is more significant.
[0119] (1.4) The applicant also studied the changing trend of the quality factor of the repaired copper micro-metal network structure at different repair times. Among them, the quality factor (Figure of Merit, referred to as FOM) is a comprehensive indicator for evaluating optoelectronic performance. It is widely used to describe the performance of transparent conductive materials. The quality factor usually combines the conductivity and light transmittance of the material to provide a unified measurement standard for the performance of the material in practical applications. It combines the two performance parameters of conductivity and light transmittance to give an evaluation of the comprehensive performance of the material. The calculation formula of the quality factor FOM is:
[0120] Wherein, T is the transmittance of the repaired micro-metal network structure, and Rs is the sheet resistance of the repaired micro-metal network structure.
[0121] In the quality factor formula, the smaller Rs is and the larger T is, the larger the quality factor (FOM) is. Therefore, if the quality factor (FOM) of the micrometal network structure is larger, it means that the micrometal network structure has both high transmittance and high conductivity. In this embodiment, the quality factor of the micrometal network structure is obtained by measuring the sheet resistance and transmittance of the micrometal network structure at different repair times.
[0122] in, Fig.10This is a graph showing the relationship between different repair times and the quality factor of the copper micrometal network structure during the repair process. Fig.10 It can be seen that during the electrochemical deposition process, the repair time is within 0min-40min. As the repair time increases, the quality factor of the repaired micro-metallic copper network structure also increases significantly from 297.84 to 28365.52. The significant increase in the quality factor proves that the transmittance and conductivity of the repaired copper micro-metallic network structure are significantly enhanced. However, after the repair time is 40min, the quality factor of the repaired copper micro-metallic network structure decreases. Fig.10 Analysis shows that in the early stage of electrochemical deposition, as the defects in the copper micrometal network structure are gradually repaired, its conductivity is significantly improved, and the change in transmittance is relatively small, so the quality factor will show a rapid growth. As the repair time is further extended, the increase in the width and thickness of the metal wires of the repaired copper micrometal network structure (mainly the increase in width) will cause the transmittance of the repaired copper micrometal network structure to decrease, thereby gradually slowing down the growth rate of the quality factor, or even slightly decreasing.
[0123] In addition, since the conductivity and transmittance of the copper micrometal network structure are usually contradictory, if the conductivity is improved by increasing the thickness of the copper micrometal network structure, the increase in thickness will also reduce the transmittance of the copper micrometal network structure. Therefore, in the actual repair process, it is also necessary to find a suitable balance between conductivity and transmittance to improve the performance of the copper micrometal network structure obtained by repair. In this embodiment, it can be combined with Figure 8 and Fig. 9 It can be seen that when the repair time of electrochemical deposition is 2 minutes, the conductivity and transmittance of the obtained copper micrometal network structure are very good, which can meet the requirements of conductivity and transmittance of these devices when preparing some devices. Therefore, it is explained that when the copper micrometal network structure is repaired in this embodiment, the repair time can be selected as 2 minutes, and the corresponding metal wire width is 8.75μm and the thickness is 3.06μm. Therefore, in actual repair, by studying the changing trend between different repair times and the width and thickness of the metal wire and the changing trend between different repair times and the square resistance and transmittance, a repair time that balances the conductivity and transmittance of the repaired copper micrometal network structure can be obtained. In the actual electrochemical deposition repair process, the repair time can be set to this value, that is, the repaired copper micrometal network structure can maintain both good conductivity and good transmittance.
[0124] 2. Comparison of some properties of the silver micrometal network structure before and after repair (2.1) Optical microscope The silver metal network structure samples before repair and the silver micro-metal network structure samples after repair were observed under an optical microscope respectively. Fig.11 The picture shown. Fig.11 The middle left picture is the SEM image of the silver micro-metal network structure before repair. Fig.11 The middle right picture is a SEM image of the silver micro-metal network structure repaired by electrochemical deposition for 60 seconds. Fig.11 Comparing the left and right images in the figure, it can be seen that there are obvious cracks and holes on the surface of the silver micrometal network structure before repair, resulting in structural discontinuity, which in turn affects the photoelectric performance of the silver micrometal network structure. The image after 60 seconds of repair shows that after electrochemical deposition repair, the cracks and defects on the surface of the silver micrometal network structure are significantly filled, the structure becomes more continuous and uniform, and the surface integrity is effectively improved. This proves that the repair method of this embodiment can effectively repair the micrometal network silver structure.
[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for repairing a micro-metal network structure based on electrochemical deposition, characterized in that: It includes the following steps: S1, according to the type of metal in the micro-metal network structure to be repaired, a corresponding electrolyte mixture is prepared, and the prepared electrolyte mixture is placed in an electrochemical deposition device with an electrolytic cell; the electrolyte mixture comprises an electrolyte solution, a complexing agent and a buffer; wherein the electrolyte solution is a substance that can provide ions corresponding to the metal to be deposited in the object to be repaired; the complexing agent is a substance that can adjust the deposition rate of the electrolyte in the aqueous solution on the micro-metal network structure to be repaired; and the buffer is used to adjust the pH value of the electrolyte mixture; S2, setting the polarization potential and repair time of the electrolytic cell according to the type of metal in the micro-metal network structure to be repaired, and placing the pretreated micro-metal network structure to be repaired in the electrolytic cell for repair; The thickness of the micro-metal network structure to be repaired in the electrolytic cell and the repair time must satisfy the following relationship: , Wherein, H is the thickness of the micro-metal network structure to be repaired; I is the current; M is the molar mass of the metal in the micro-metal network structure to be repaired; t is the repair time of the micro-metal network structure to be repaired in the electrolytic cell; n is the amount of metal in the micro-metal network structure to be repaired; F is the Faraday constant; A is the surface area of the micro-metal network structure to be repaired; S3, determining whether the micro-metal network structure in the electrolytic cell has been repaired; if so, taking it out of the electrolytic cell, otherwise repeating step S2 to repair it again until the micro-metal network structure is repaired.
2. The method for repairing a micro-metal network structure based on electrochemical deposition according to claim 1, characterized in that: The judgment standard for the completion of repair is any of the following methods: (i) current observation method: by observing the current in the electrolytic cell, when the current in the electrolytic cell changes little and tends to be stable, it means that the micro-metal network structure to be repaired has been repaired; (ii) local conductivity test method: the conductivity of the repaired area in the micro-metal network structure is measured by the four-probe method; When the conductivity of the repaired area in the micrometal network structure meets the conductivity requirements after repair, it means that the micrometal network structure to be repaired has been repaired; (iii) Microscope observation method: Observe the repaired micrometal network structure through a scanning electron microscope or an optical microscope. If the repaired micrometal network structure is a continuous and uniform structure, it means that the micrometal network structure to be repaired has been repaired.
3. The method for repairing a micro-metal network structure based on electrochemical deposition according to claim 1, characterized in that: The sheet resistance of the repaired micrometal network structure is less than 1Ω / sq.
4. The method for repairing a micro-metal network structure based on electrochemical deposition according to claim 1, characterized in that: The electrolyte mixture in the electrolytic cell needs to be continuously stirred when the electrochemical deposition is performed.
5. The method for repairing a micro-metal network structure based on electrochemical deposition according to claim 1, characterized in that: The micro-metal network structure needs to be pre-treated before repair; the pre-treatment includes the following steps: The micro-metal network structure to be repaired is ultrasonically cleaned with deionized water, then cleaned with anhydrous ethanol, and blown dry with nitrogen after cleaning; finally, plasma cleaning is performed; the deionized water cleaning time is 10min-50min, the anhydrous ethanol cleaning time is 5min-10min; the plasma cleaning time is 10min, and the cleaning power is 40W.
6. The method for repairing a micro-metal network structure based on electrochemical deposition according to claim 1, characterized in that: The components of the micro-metal network structure to be repaired include any single substance among gold, silver, aluminum, copper, platinum, nickel and titanium.
7. The method for repairing a micro-metal network structure based on electrochemical deposition according to claim 1, characterized in that: The temperature range of the electrolytic cell is 25°C to 35°C; And / or, the current density in the electrolytic cell is 5 mA / cm 2 ~20mA / cm 2 .
8. The method for repairing a micro-metal network structure based on electrochemical deposition according to claim 1, characterized in that: The electrochemical deposition equipment is an electrochemical workstation with a three-electrode system. A working electrode, a counter electrode and a reference electrode are arranged in the electrolytic cell. The working electrode, the counter electrode and the reference electrode are respectively connected to the three electrodes in the electrochemical workstation. The micro-metal network structure to be repaired serves as the working electrode; the reference electrode is an Ag / AgCl electrode; the counter electrode is a 99.9% metal foil, and the metal type of the metal foil in the counter electrode is the same as the metal type of the micro-metal network structure to be repaired.
9. The method for repairing a micro-metal network structure based on electrochemical deposition according to claim 8, characterized in that: The working electrode and the counter electrode are both fixed in the electrolytic cell by an electrode clamp, and the distance between the working electrode and the counter electrode is 2 cm to 8 cm.
10. The method for repairing a micro-metal network structure based on electrochemical deposition according to claim 9, characterized in that: The electrode clamp is a Pt electrode clamp.
Citation Information
Patent Citations
Nanometal-assisted directional electroplating and electrolysis line forming and repairing method
CN113207237A
Method for repairing concrete crack by inducing ettringite through electric field
CN114538957A
Apparatus for modification of concrete crack by electrochemical deposition
CN2861375Y
Deposition of metals onto nanotube transparent conductors
US20090068241A1
Cited By
Vehicle windshield and preparation method thereof, vehicle windshield assembly and automobile
CN120572906A
Vehicle windshield and method for manufacturing the same, vehicle windshield assembly, and automobile
CN120572906B